BRAIN-SKETCHING TECHNIQUE FOR DESCRIPTIVE TEXT IN IMPROVE WRITING SKILL AT SENIOR HIGH SCHOOL OF UNISMUH MAKASSAR - Erwin Akib (Universitas Muhammadiyah Makassar, 2012)
The research aimed at improving the ability of the Eleventh-grade students of Senior High School of Unismuh Makassar in writing descriptive text using the Brain-Sketching Technique. For the purpose, it employed Classroom Action Research in which the researcher worked in planning, implementation, observation, and reflection on the data collected from the teaching and learning process and the students' writing products. The method of this research is Classroom Action Research that consists of two cycles. One cycle consisted of four meetings. It means that there were eight meetings for two cycles. This classroom action research was done in Senior High School of Unismuh Makassar for English subject. As subjects in this research are class XI IPA 2 in 2012-2013 academic years which consists of 26 students. Those consisted of 14 women and 12 men. The instruments used were writing test and observation sheet. The study was conducted in a diagnostic test, cycle one and cycles two, each cycle was carried out in four meetings. The objective of the research was intended to know the improvement of the students’ writing ability after using Brain-Sketching Technique at the Eleventh-grade students of Senior High School of Unismuh Makassar. The findings indicated that using Brain-Sketching Technique could improve the students' ability in writing descriptive text. Before giving implementation the researcher gave the students diagnostic test and the mean score of diagnostic test was 63.90 as classification “fairly good”. Then the researcher conducted the first cycle and the second cycles, and the result showed that the students' scores in the first and second cycles improved. In the first cycle, the mean score of students was 67.22 as classification “fairly good”, meanwhile the mean score of students in the second cycle was 71.41 as classification “good. It means that the improvement of students’ writing ability from D-Test to cycle I was 5.21%, the cycle I to cycle II was 6.22%, D- test to cycle II was 11.73%. Keywords: Brain-Sketching, Technique, Descriptive, Text, Writing.